2008
DOI: 10.1093/treephys/28.9.1365
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of low-temperature acclimation in temperate and boreal conifer foliage in a mild winter climate

Abstract: To provide baseline data for physiological studies of extreme low-temperature (LT) tolerance in boreal conifers, we profiled LT stress responses, liquid nitrogen (LN(2))-quench tolerance, and sugar concentrations in foliage of boreal-temperate species pairs in the genera Abies, Picea and Pinus, growing in an arboretum in a temperate oceanic climate from August 2006 through April 2007. The boreal species acclimated more rapidly and deeply than the temperate species, acquiring LN(2)-quench tolerance by late Nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
86
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(94 citation statements)
references
References 33 publications
8
86
0
Order By: Relevance
“…4D, inset), but persisted only in the LTAC treatment. In general, Glc and Fru are only observed in minor quantities in conifer needles (Hoch et al, 2003;Strimbeck et al, 2008) because they act as transitory intermediates in Suc synthesis, glycolysis, and regeneration of triose phosphates in the Calvin cycle (Granot et al, 2013). The relatively small but significant increase in Glc and Fru levels in LTAC seedlings clearly suggests an impairment of metabolic activity by low temperature.…”
Section: A Major Shift In Carbohydrate Metabolism Is Induced By Shortmentioning
confidence: 99%
See 2 more Smart Citations
“…4D, inset), but persisted only in the LTAC treatment. In general, Glc and Fru are only observed in minor quantities in conifer needles (Hoch et al, 2003;Strimbeck et al, 2008) because they act as transitory intermediates in Suc synthesis, glycolysis, and regeneration of triose phosphates in the Calvin cycle (Granot et al, 2013). The relatively small but significant increase in Glc and Fru levels in LTAC seedlings clearly suggests an impairment of metabolic activity by low temperature.…”
Section: A Major Shift In Carbohydrate Metabolism Is Induced By Shortmentioning
confidence: 99%
“…As a consequence, carbon demand in sink tissue decreases toward the end of the growing season, and the bulk of photoassimilate is translocated from source tissues to storage tissues (Hansen and Beck, 1994;Oleksyn et al, 2000). In addition, cryoprotective soluble sugars, including sucrose, raffinose, and pinitol, accumulate in leaf tissues to enhance freezing tolerance (Strimbeck et al, 2008;Angelcheva et al, 2014). Thus, by winter, leaf nonstructural carbohydrates are mainly comprised of mono-and oligosaccharides, and only minimal levels of starch remain (Hansen and Beck, 1994;Strimbeck et al, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a conclusion, the accessions showing notably reduced photosynthetic efficiency, and particularly clone 52 which showed only 75.45% of the control F v /F m , can be considered more susceptible to freezing damage to PSII after hardening development. Measurement of electrolyte leakage was employed to quantify cold damage to cellular membranes (Hong et al 2009;Strimbeck et al 2008). Broad variation was observed among the cypress plants studied (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Correlation between electrolyte leakage and resistance to various abiotic stresses has been established in many plant species. Based on temperature-relative electrolyte leakage curves, Strimbeck et al 2008 showed that boreal species in the coniferous genera Abies, Picea, and Pinus were capable of more rapid and efficient cold acclimation than the corresponding temperate ones. Interspecific hybrids between Pinus strobus and Pinus wallichiana presented differences in freezing-induced electrolyte leakage in different acclimation stages (Lu et al 2007).…”
Section: Discussionmentioning
confidence: 99%